Synthesis of Polyaniline Under Electrolytic Plasma on Carbon Fiber Fabric. Issue 1 (16th December 2020) - Kunicki, Lucas; Becker, Daniela; Fontana, Luis C.; Dalmolin, Carla
Abstract: Polyaniline is synthetized on carbon fiber through electrolytic plasma applied in an acid monomer solution, without an oxidant. Pulsed‐plasma carbon fiber surface treatment is performed with two 1.0 kV pulses for 1 µs with an 200 µs off period. Different treatment times and ultrasound presence, to create microbubbles that can help plasma formation, are tested. The ultrasonic bath is not effective to produce higher quantities of polymer. Furthermore, the film formed on the carbon fiber is chemically characterized through treatment in a basic solution followed by immersion in NMP, and through FT‐IR and XPS. The presence of nitrogen in the carbon fiber surface and the characteristic FT‐IR bands of delocalized electrons indicate that the electrolytic plasma treatment is efficient to synthesize polyaniline in its conducting form. Electrochemical activity is accessed by cyclic voltammetry, indicating the formation of electrodes with good reversibility and stability, thereby suitable for supercapacitor applications.